2013
DOI: 10.2304/ciec.2013.14.2.155
|View full text |Cite
|
Sign up to set email alerts
|

From Choice to Change: An Analysis of the ‘choice’ Discourse in Canada's 2006 Federal Election

Abstract: A critical discourse analysis (CDA) was used to analyze the representation of Early Childhood Education and Care (ECEC) in the 2006 federal election in Canada. Guided by Fairclough's approach to CDA, this study analyzed written documents including newspaper articles from The Globe and Mail and The National Post, the policy platforms of the Liberal and Conservative parties, and political speeches from party leaders. Four textual and discourse processes were found to legitimize the 'choice' discourse and contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 6 publications
0
18
0
Order By: Relevance
“…These two funding mechanisms are promoted by the government to facilitate parents ' choice for formal or informal childcare within the mixed market (Richardson et al . ). As discussed earlier, and suggested in the examples above, public funding for in‐home childcare does not necessarily indicate public responsibility or the formalization of services.…”
Section: The Intersection Of Ecec and Migration Policymentioning
confidence: 97%
“…These two funding mechanisms are promoted by the government to facilitate parents ' choice for formal or informal childcare within the mixed market (Richardson et al . ). As discussed earlier, and suggested in the examples above, public funding for in‐home childcare does not necessarily indicate public responsibility or the formalization of services.…”
Section: The Intersection Of Ecec and Migration Policymentioning
confidence: 97%
“…On the other hand, while ECEs obtained professionalization, their equal status as partners with OCTs in the classroom is fundamentally untrue. Although both the teaching and ECE professions are characterized by feminization, OCTs have been discursively characterized as educators, while ECEs have been framed as care workers within a neoliberal context that devalues care work (Langford, Powell, & Bezanson, 2020;Richardson et al, 2013).…”
Section: Race-ing Eces and Octsmentioning
confidence: 99%
“…This major research paper identified the "choice" discourse, rooted in a conservative ideology favouring the stay-at-home-mom family model, as the dominant representation of childcare. Richardson, Langford, Friendly & Rauhala (2013) went on to problematize this narrow conceptualization and representation of childcare suggesting that emotionally laden ideologies overshadowed rational and critical policy debates in the media.…”
Section: Literature Review: Childcare Policy Representation In the Canadian Pressmentioning
confidence: 99%